Synthesis, Molecular Structure, Thermal and Spectroscopic Analysis of a Novel Bromochalcone Derivative with Larvicidal Activity - Pollyana P. Firmino; Jaqueline E. Queiroz; Lucas D. Dias; Patricia R. S. Wenceslau; Larissa M. de Souza; Ievgeniia Iermak; Wesley F. Vaz; Jean M. F. Custódio; Allen G. Oliver; Gilberto L. B. de Aquino; Hamilton B. Napolitano (Crystals, 2022)
Chalcones belong to the flavonoids family and are natural compounds which show promising larvicidal property against Aedes aegypti larvae. Aiming to obtain a synthetic chalcone derivative with high larvicidal activity, herein, a bromochalcone derivative, namely (E)-3-(4-butylphenyl)-1-(4-bromophenyl)-prop-2-en-1-one (BBP), was designed, synthesized and extensively characterized by 1H- and 13C- nuclear magnetic resonance (NMR), infrared (IR), Raman spectroscopy, mass spectrometry (MS), ultraviolet–visible spectroscopy (UV-Vis), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), and X-ray diffraction. Further, the quantum mechanics calculations implemented at the B3LYP/6–311+G(d)* level of the theory indicate that the supramolecular arrangement was stabilized by C–H⋯O and edge-to-face C–H⋯π interactions. The EGAP calculated (3.97 eV) indicates a good reactivity value compared with other similar chalcone derivatives. Furthermore, the synthesized bromochalcone derivative shows promising larvicidal activity (mortality up to 80% at 57.6 mg·L−1) against Ae. aegypti larvae.